Editorial: let's take a break from studying the PPI‐fracture association—Authors' reply. Issue 11 (17th May 2018) - Torvinen‐Kiiskinen, S.; Tolppanen, A.‐M.; Koponen, M.; Tanskanen, A.; Tiihonen, J.; Hartikainen, S.; Taipale, H.
Abstract : Linked Content This article is linked to Torvinen‐Kiiskinen et al and Targownik papers. To view these articles visithttps://doi.org/10.1111/apt.14589 andhttps://doi.org/10.1111/apt.14640 .